The Paradox of Control: Visual Clue vs. Auditory Instruction in Game Designing - Yusup Sigit Martyastiadi (Graduate School of Institut Seni Indonesia Yogyakarta, 2018)
Visual clue and auditory instruction are information that used in games. the genuine information is developed on game design conceptualization. this paper explains the study of the paradox of control, which was applied in the process of game designing. Basically, the research investigates the differences of powerful game information between visual clue and auditory instruction to gain complexity of game levelling. the research method used game design experiments, playing observations, and the interview to clarify the respondents’ decision-making. the visual clues and auditory instructions were occurred randomly based on the path of the respondents’ chosen. However, in one level of observation, the information of visual clue & auditory instruction were happening together in the same time and those were contradictive each other. this condition was called the paradox of control on information handling in the game. interestingly, in this circumstance, most of the respondents decided to follow the visual clues, although it was not the right direction. that condition potentially led by visual perception. this paper will describe the respondents’ motivation on their decision-making. Finally, the result of this study could give recommendation for level designers in game designing, especially on complexity of the challenge in the game’s dramatic element.